Relations between food intake, psychological distress, and gastrointestinal symptoms: A diary study. Issue 7 (1st August 2019) - Clevers, Egbert; Törnblom, Hans; Simrén, Magnus; Tack, Jan; Van Oudenhove, Lukas
Abstract : Background: Gastrointestinal symptoms can be triggered by food intake and psychological distress, but individual‐level research on food–symptom and stress–symptom associations is scarce. Objective: We aimed to identify associations between food intake, psychological distress and gastrointestinal symptoms, and their implications for personalised clinical management. Methods: Through the mobile phone application mySymptoms, 163 users kept, for a median of five weeks, a diary of food intake, psychological distress and gastrointestinal symptoms. We quantified associations between these on the individual level. The presence of individual‐level associations was compared over latent classes of daily symptom patterns. Results: Various gastrointestinal symptoms had demonstrable food–symptom associations (heartburn: 73%, discomfort: 67%, diarrhoea: 57%, bloating: 53%, and gas: 48%). Food–symptom associations for pain in the abdomen (33%) were concentrated in the latent class of individuals with pain in the morning (68%), rather than those with pain in the evening and night (27% and 10%, respectively, p  < 0.001). Stress–symptom relations were also found, although only 18% of individuals reported psychological distress. Conclusion: Personal food–symptom and stress–symptom relations can be detected, and may translate into specific daily symptom patterns. A next step will be to let personal food–symptom and stress–symptom relations serve as the basis for personalised clinical management.